Conformal CVD of WO3−x on electrospun carbon nanofiber mats assisted by Joule heating. (15th August 2022) - Cisquella-Serra, Albert; Magnani, Marco; Madou, Marc; Gamero-Castaño, Manuel
Abstract: This article presents a novel technique for building carbon nanofiber composites using chemical vapor deposition (CVD) assisted by Joule heating. The heating of electrospun carbon nanofibers mats, induced by the passing of an electric current through the resistive mat and the associated Joule heating, is studied using infrared thermography. The standard deviation of the resulting temperature field is smaller than 5% of its average value, a result explained by the homogeneous and two-dimensional nature of the mat, as well as by the dominance of radiative heat transport over thermal conduction. A thermal model is developed to correlate the imposed electrical dissipation and the temperature of the mat, a key variable in CVD. Joule heating is used to decompose W(CO)6 and deposit a coating of WO3− x on all carbon nanofibers without the need of annealing. The coating is conformal, uniform along the nanofiber and across the mat, and its thickness is controlled with the voltage difference applied across the mat. Because of the wide range of temperatures that can be imposed and the variety of precursors that can be employed, CVD assisted by Joule heating is a promising method for developing new carbon composites. Graphical abstract: Image 1 Highlights: A method for making a mat of carbon nanofibers with a CVD coating of WO3− x . CVD is triggered and easily controlled by passing electric current through the mat. The WO3− x coating is conformal, homogeneous and does not require annealing.